Young athletes' perceptions of the role of their mothers in their sport career - Miriam Palomo Nieto; Luis Miguel Miguel Ruiz Perez; Mauro Sánchez Sánchez; Virginia García Coll (Asociación Española de Ciencias del Deporte, 2011)
The aim of the study was to examine the role played by mothers in the development of their young sons and daughters. Participants were four Spanish young athletes competing at international level and their mothers. The athletes were interviewed and the interviews were analysed following the guidelines of the Grounded Theory (Strauss and Corbin, 1998). This approach revealed how participants perceived the role played by their mothers in their athlete career. According to these perceptions, athletes considered that their mothers' role was heavily centred on their unconditional support. This unconditional support was later itemized into a series of additional aspects. Our results concerning the factors with an impact on the development of sports excellence are coincidental with those of other authors. Sadly, there is very little literature on the issue and, consequently, our findings are difficult to check against other surveys. Our results, nevertheless, reveal the enormous influence the mother's role has on the development of talented athlete children. Key Words: Social support, Sports Excellence, Family, Talent, Grounded Theory